DIPLOMASI INDONESIA TERHADAP AUSTRALIA DALAM PENYELESAIAN KASUS PENCEMARAN MINYAK MONTARA DI PERAIRAN LAUT TIMOR PERIODE 2009-2017 - Ondiffa Putri Claresta, - (2018)
This research discusses Indonesia Diplomacy Against Australia in the Montara Oil Pollution case resolution in the waters of the Timor Sea Period 2009-2017. Montara oil pollution is causing economic losses as well as the pollution of the marine environment in the waters of Indonesia. The purpose of this research is to explain the problems of oil pollution in the waters of Indonesia and analyzes the process of diplomacy between montara oil pollution settlement Indonesia and Australia in the period 2009-2017. This research uses qualitative research methods with types of descriptive research. The framework of thought on this research uses theories of diplomacy, international security theory and the concept of pollution of the sea. The results of this study showed the levels of diplomacy conducted by the Indonesia settlement ranging from Australia to communicate and PTTEP Australasia and also affect the meeting in an effort to tackle the negotiation the pollution happened and losses experienced by the people of Indonesia around East Nusa Tenggara waters are polluted. Then the last attempt was done by Indonesia are advocacy efforts toward the oil company PTTEP Australasia